2023
DOI: 10.1021/acsami.2c15054
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Tetrahedral Site Occupancy by the Zn Dopant in Li-NMCs toward High-Voltage Compositional–Structural–Mechanical Stability via Operando and 3D Atom Probe Tomography Studies

Abstract: Ni-containing “layered”/cation-ordered LiTMO2s (TM = transition metal) suffer from Ni-migration to the Li-layer at the unit cell level, concomitant transformation to a spinel/rock salt structure, hindrance toward Li-transport, and, thus, fading in Li-storage capacity during electrochemical cycling (i.e., repeated delithiation/lithiation), especially upon deep delithiation (i.e., going to high states-of-charge). Against this backdrop, our previously reported work [ACS Appl. Mater. Interfaces 2021, 13, 25836–258… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…It can be seen that techniques commonly used to characterize cation disorder now mainly rely on the comparison between ordered and disordered samples, while a more direct way to probe cation arrangements is still lacking. Techniques such as high-resolution transmission electron microscopy (HRTEM) or atom probe tomography (APT), 75 which can visualize different atoms with sub-nanometer resolution, can be useful for more directly characterizing cation disorder. However, the critical challenge for these techniques will be to characterize the materials without altering them during sample preparation or during the measurement itself.…”
Section: Quantifying and Comparing Cation Disordermentioning
confidence: 99%
“…It can be seen that techniques commonly used to characterize cation disorder now mainly rely on the comparison between ordered and disordered samples, while a more direct way to probe cation arrangements is still lacking. Techniques such as high-resolution transmission electron microscopy (HRTEM) or atom probe tomography (APT), 75 which can visualize different atoms with sub-nanometer resolution, can be useful for more directly characterizing cation disorder. However, the critical challenge for these techniques will be to characterize the materials without altering them during sample preparation or during the measurement itself.…”
Section: Quantifying and Comparing Cation Disordermentioning
confidence: 99%
“…The operando XRD tests and the Rietveld refinement results confirmed that Co doping can extend the lattice and decrease particle size, which is conducive to cathodic reactions and promotes synergistic catalytic effects, and then improve electrochemical performance. [118] To investigate the influence of Zn doping on the structural-mechanical-compositional integrity of Li-TM-oxide-based cathode materials (Li-NMC) after deep lithium removal, operando XRD was used to systematically study the changes of lattice parameters (Figure 7B) by Sharma et al [119] Typically, serious structural degradation occurs for Ni-rich cathode materials when operated in high-temperature condition, which often leads to severe performance degradation. Lee.…”
Section:  Xrd For Resolving Crystalline Structurementioning
confidence: 99%
“…[ 118 ] To investigate the influence of Zn doping on the structural‐mechanical‐compositional integrity of Li‐TM‐oxide‐based cathode materials (Li‐NMC) after deep lithium removal, operando XRD was used to systematically study the changes of lattice parameters (Figure 7B) by Sharma et al. [ 119 ] Typically, serious structural degradation occurs for Ni‐rich cathode materials when operated in high‐temperature condition, which often leads to severe performance degradation. Lee.…”
Section: Application Examples Of Battery Structure Detectionmentioning
confidence: 99%
See 1 more Smart Citation